The Direct and Indirect Effects of Offender Drug Use on Federal Sentencing Outcomes - Spohn, Cassia (Journal of quantitative criminology, 2014)
Objectives The federal sentencing guidelines constrain decision makers’ discretion to consider offenders’ life histories and current circumstances, including their histories of drug use and drug use at the time of the crime. However, the situation is complicated by the fact that judges are required to take the offender’s drug use into account in making bail and pretrial detention decisions and the ambiguity inherent in decisions regarding substantial assistance departures allows consideration of this factor. In this paper we build upon and extend prior research examining the impact of an offender’s drug use on sentences imposed on drug trafficking offenders. Methods We used data from three U.S. District Courts and a methodologically sophisticated approach (i.e., path analysis) to test for the direct and indirect (i.e., through pretrial detention and receipt of a substantial assistance departure) effects of an offender’s drug use history and use of drug at the time of the crime, to determine if the effects of drug use varies by the type of drug, and to test for the moderating effect of type of crime. Results We found that although the offender’s history of drug use did not affect sentence length, offenders who were using drugs at the time of the crime received longer sentences both as a direct consequence of their drug use and because drug use at the time of the crime increased the odds of pretrial detention and increased the likelihood of receiving a substantial assistance departure. We also found that the effects of drug use varied depending on whether the offender was using crack cocaine or some other drug and that the type of offense for which the offender was convicted moderated these relationships. Conclusions Our findings illustrate that there is a complex array of relationships between drug use and key case processing decisions in federal courts.